Hematopoietic stem cell transplantation and quality of life during the first year of treatment - Angela da Costa Barcellos Marques; Ana Paula Szczepanik; Celina Angélica Mattos Machado; Pâmella Naiana Dias Santos; Paulo Ricardo Bittencourt Guimarães; Luciana Puchalski Kalinke (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate the quality of life of adult patients with hematological cancer comparing Hematopoietic Stem Cell Transplantation modalities during the first year of treatment. Method: this is an observational and longitudinal research with 55 participants. Data collection was performed in six steps: before transplantation, pancytopenia, before hospital discharge, after 100, 180 and 360 days, in a reference hospital in Brazil for this treatment. The international instruments Quality of Life Questionnaire - Core 30 and Functional Assessment Cancer Therapy - Bone Marrow Transplantation were validated and translated into Portuguese (Brazil). Results: the mean age of participants was 36 years, 65% (n = 36) had leukemia diagnosis and 71% (n = 39) had undergone allogenic transplantation. In the Quality of Life Questionnarie - Core30 instrument, the pain symptom was significant between the first and second stages, and loss of appetite between the third and fourth stages, both in the allogenic group. In the Functional Assessment Cancer Therapy - Bone Marrow Transplantation, the functional well-being domain was significant between the third and fourth stages, also in the allogenic group. Conclusions: although the aggressiveness of treatment affects quality of life, patients consider it satisfactory after the first year. There are few significant differences between autologous and allogenic patients, and both groups have recovered in the course of the process.